Analisis Model Pendidikan Politik Partai Solidaritas Indonesia (PSI) dalam Meningkatkan Partisipasi Politik Kaum Muda di Kabupaten Wonosobo - Sahrul Said; Dwian Akta Padma Eldo (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Political education is a strategic function of political parties in enhancing the quality of civic participation, particularly among young people. This study aims to analyze the political education model implemented by the Indonesian Solidarity Party (PSI) in Wonosobo Regency and to assess its effectiveness in promoting youth political participation. The research employs a qualitative case study approach using in-depth interviews, observation, and document analysis. The findings reveal that PSI has developed a participatory and contextual political education model by integrating offline and online strategies and positioning party cadres as key educational actors. This model contributes to improved political understanding, attitudinal change, and the early emergence of youth political participation, although it remains constrained by digital literacy gaps and limited cadre capacity. The study highlights the importance of sustainable and adaptive party-based political education in strengthening local democracy.